2018
DOI: 10.20964/2018.06.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroformed Fe-Ni Substrate Textures on Light-trapping in Thin Film Solar Cells

Abstract: Electroforming can be used to separate electrodeposited metal from the surface of a metal or other conductive material to produce new metallic products with fine shapes. Because Si thin-film solar cells possess fewer absorption layers than other compound thin-film solar cells, light-trapping technology is required to increase the rate of light absorption. Various metal substrate shapes can be constructed in the electroforming process, depending on the shape of the mandrel surface. The objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The deposition process was conducted under a DC condition (60 mA cm −2 ). First, nc Ni‐49 at% Fe alloy films were deposited over the cathode surface at thicknesses of up to 200 ± 10 μm and then mechanically stripped as free‐standing foils 9 . Subsequently, the as‐deposited foils were annealed in an H 2 + N 2 gas atmosphere at 320, 350 and 370°C at a 5°C/min heating rate, and this was followed by a 60‐min holding time to thermally stabilise the nc alloys.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition process was conducted under a DC condition (60 mA cm −2 ). First, nc Ni‐49 at% Fe alloy films were deposited over the cathode surface at thicknesses of up to 200 ± 10 μm and then mechanically stripped as free‐standing foils 9 . Subsequently, the as‐deposited foils were annealed in an H 2 + N 2 gas atmosphere at 320, 350 and 370°C at a 5°C/min heating rate, and this was followed by a 60‐min holding time to thermally stabilise the nc alloys.…”
Section: Methodsmentioning
confidence: 99%
“…1 The potential applications of nc Ni-Fe alloys range from micro-electro-mechanical systems to solar cells, organic light-emitting diodes, magnetic devices and functional coatings, in force of their unique magnetic, thermal and mechanical properties. [2][3][4][5][6][7][8][9] Despite the versatility of the electrodeposition process, in terms of alloy types, chemical compositions, microstructure and properties, 1 process control is difficult as a result of such factors as the bath composition, current density, pH and temperature. The fabrication of nc Ni-Fe alloys by means of the DCelectrodeposition process, in its simplest form, utilises a constant current density ( j).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This electroforming process can manufacture metallic products in fine shapes (µm to mm scale) by separating the electrodeposited metal from the surface of a metal or a conductive material. [ 29,30 ] Thus, it has been reported that the metal products with complex and precise patterns were fabricated on a large scale by the electroforming method using Ni, Cu, Au, and Fe‐Ni alloys. [ 31–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Structures with sizes comparable to the wavelengths of incident light selectively diffract the light to cause constructive or destructive shapes (µm to mm scale) by separating the electrodeposited metal from the surface of a metal or a conductive material. [29,30] Thus, it has been reported that the metal products with complex and precise patterns were fabricated on a large scale by the electroforming method using Ni, Cu, Au, and Fe-Ni alloys. [31][32][33] Therefore, we developed the Bragg stacked Ni textures with a µm pitch to cost-effectively reproduce biomimetic structural colors of the Papilio Palinurus on a large scale.…”
Section: Introductionmentioning
confidence: 99%